위성영상 기반 해양수산 양식장의 경계 데이터 추출 - 정성훈; Seong-hoon Jeong (한국항행학회논문지, 2023)
선박의 안전 운항과 해양수산 양식장 관리를 위해 해양수산 빅데이터 구축에 필요한 해양수산 양식장의 경계를 추출한 데이터 셋은 어장 허가 구역과의 일치 여부 조사를 통해 선박의 운항 경로에 불법 설치 시 장애물 정보를 미리 제공할 수 있다. 또한, 해양사고 등에 의한 피해보상을 위해 필요한 양식장 조업 여부도 파악할 수 있으며, 해당 지자체에서는 어장도와의 중첩 비교를 통해 어장 관리 등에 사용할 수 있다. 선박의 안전 운항을 위한 전자해도에 물표 표시를 통해 운항 경로상의 장애물 파악에 필요한 기초 데이터로써 활용이 높다. 이 연구에서는 양식장의 경계 추출을 위해 충분한 공간해상도를 가지며 짧은 주기로 반복하여 촬영하는 유럽항공우주국(ESA; europe space agency)의 Sentinel-2 위성영상 자료를 사용하였다. 영상 이미지에서 양식장의 주기별 현황 데이터의 생산을 위해 해상의 구역별 데이터를 부산권, 울산권, 거제·창원권, 고성·통영권, 남해·사천권의 5개 관리 구역으로 나누어 처리하였으며, 구역별 위성영상의 수집과 영상의 강조 처리 과정을 거쳐 양식장의 경계 데이터와 메타정보를 추출하였다. For safe operation of ships and management of marine fisheries farms, the data set that extracts the boundaries of marine fisheries farms can provide information on obstacles in the vessel's navigation path in advance by examining whether it matches the fishing ground permit area. In addition, it can be used to determine whether fish farms are operating to compensate for damage caused by marine accidents, and the relevant local government can use it to manage fishing grounds. It is also highly utilized as basic data to identify obstacles for safe navigation of ships. In this study, Sentinel-2 satellite image data from the European Space Agency (ESA) was used to extract the boundaries of fish farms. From the video image, the fish farm's status data by cycle was divided into five zones: Busan-Ulsan area, Geoje-Changwon area, Goseong-Tongyeong area, and Namhae-Sacheon area. Through the image highlighting process, the farm boundary data and meta data were processed and extracted.